2020
DOI: 10.1038/s41396-020-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation reduces maternal defensive inflammation and predicts a gut bacteriome with reduced immune priming capacity in infants

Abstract: Habitual supplementation of fish oil is thought to provide benefits to the developing infant; however, the effects on infant microbial establishment and immune development are unknown. A 6-month observational cohort study was conducted where 47 out of 91 women self-administered dietary fish oil during breastfeeding. Infant stool and mothers’ breast milk were collected each month over 6 months. Gas chromatography was used to quantify breast milk fatty acids and high-throughput sequencing was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Compared with sunflower oil, the dietary intake of fish oil exerted the greatest effect on the diversity of the intestinal flora [ 13 ]. High levels of omega-3 PUFAs in fish oil cause significant changes in the gut microbiota, which might explain the health benefits of its use [ 14 ]. In addition, fish oil exerts an inhibitory effect on a variety of bacteria.…”
Section: Omega-3 Pufas and The Gut Microbiotamentioning
confidence: 99%
“…Compared with sunflower oil, the dietary intake of fish oil exerted the greatest effect on the diversity of the intestinal flora [ 13 ]. High levels of omega-3 PUFAs in fish oil cause significant changes in the gut microbiota, which might explain the health benefits of its use [ 14 ]. In addition, fish oil exerts an inhibitory effect on a variety of bacteria.…”
Section: Omega-3 Pufas and The Gut Microbiotamentioning
confidence: 99%
“…A diet rich in omega-3 PUFA, such as seafood, deep-sea fish (salmon, mackerel, sardines), nuts, and seeds, has several beneficial effects on the gut microbiota [ 83 ]. Consumption of such a diet leads to a decrease in the growth of Enterobacteria and an increase in the growth of Bifidobacteria [ 84 , 85 ]. Furthermore, the consumption of omega-3 PUFA leads to an increased production of anti-inflammatory mediators and the inhibition of pro-inflammatory mediators, which has a positive effect on microbiome modulation [ 82 ].…”
Section: Modulation Of the Microbiomementioning
confidence: 99%
“…The n-3PUFA could directly modulate the diversity of the gut microbiota. Previous studies have shown that the intake of fish oil affects the diversity of the intestinal microbiota in trout and infants 34,35 . In this study, the intake of EPA-EE and DHA-EE reduced the alpha diversity of fecal microbiota, which is different from that found in previous reports 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the intake of fish oil affects the diversity of the intestinal microbiota in trout and infants 34,35 . In this study, the intake of EPA-EE and DHA-EE reduced the alpha diversity of fecal microbiota, which is different from that found in previous reports 34,35 . In this experiment, EPA-EE and DHA-EE both more than 99 pure were used as n-3PUFA sources; however, previous studies used fish oil.…”
Section: Discussionmentioning
confidence: 99%